Efficacy and safety of a hexanic extract of Serenoa repens (Permixon®) for the treatment of lower urinary tract symptoms associated with benign prostatic hyperplasia (LUTS/BPH): systematic review and meta‐analysis of randomised controlled trials and observational studies. (6th June 2018) - Vela‐Navarrete, Remigio; Alcaraz, Antonio; Rodríguez‐Antolín, Alfredo; Miñana López, Bernardino; Fernández‐Gómez, Jesús M.; Angulo, Javier C.; Castro Díaz, David; Romero‐Otero, Javier; Brenes, Francisco J.; Carballido, Joaquín; Molero García, José Mª; Fernández‐Pro Ledesma, Antonio; et al.
Abstract : Objectives: To comprehensively evaluate the efficacy and safety of the hexanic extract of Serenoa repens (HESr, Permixon ® ; Pierre Fabre Médicament, Castres, France), at a dose of 320 mg daily, as monotherapy for the treatment of lower urinary tract symptoms associated with benign prostatic hyperplasia (LUTS/BPH). Materials and methods: We conducted a systematic review and meta‐analysis of randomised controlled trials (RCTs) and prospective observational studies in patients with LUTS/BPH identified through searches in Medline, Web of Knowledge (Institute for Scientific Information), Scopus, the Cochrane Library, and bibliographic references up to March 2017. Articles studying S. repens extracts other than Permixon were excluded. Data were collected on International Prostate Symptom Score (IPSS), maximum urinary flow rate (Qmax ), nocturia, quality of life, prostate volume, sexual function, and adverse drug reactions (ADRs). Data obtained from RCTs and observational studies were analysed jointly and separately using a random effects model. A sub‐group analysis was performed of studies that included patients on longer‐term treatment (≥1 year). Results: Data from 27 studies (15 RCTs and 12 observational studies) were included for meta‐analysis (total N = 5 800). Compared with placebo, the HESr was associated with 0.64 (95% confidence interval [CI] −0.98 to −0.31) fewer voids/night ( P < 0.001) and an additional mean increase in Qmax of 2.75 mL/s (95% CI 0.57 to 4.93; P = 0.01). When compared with α‐blockers, the HESr showed similar improvements on IPSS (weighted mean difference [WMD] 0.57, 95% CI −0.27 to 1.42; P = 0.18) and a comparable increase in Qmax to tamsulosin (WMD −0.02, 95% CI −0.71 to 0.66; P = 0.95). Efficacy assessed using the IPSS was similar after 6 months of treatment between the HESr and 5α‐reductase inhibitors (5ARIs). Analysis of all available published data for the HESr showed a mean improvement in IPSS from baseline of −5.73 points (95% CI −6.91 to −4.54; P < 0.001). HESr did not negatively affect sexual function and no clinically relevant effect was observed on prostate‐specific antigen. Prostate volume decreased slightly. Similar efficacy results were seen in patients treated for ≥1 year ( n = 447). The HESr had a favourable safety profile, with gastrointestinal disorders being the most frequent ADR (mean incidence of 3.8%). Conclusion: The present meta‐analysis, which includes all available RCTs and observational studies, shows that the HESr (Permixon) reduced nocturia and improved Qmax compared with placebo and had a similar efficacy to tamsulosin and short‐term 5‐ARI in relieving LUTS. HESr (Permixon) appears to be an efficacious and well‐tolerated therapeutic option for the long‐term medical treatment of LUTS/BPH.